Photon Versus Proton Beam Therapy for T1–3 Squamous Cell Carcinoma of the Thoracic Esophagus Without Lymph Node Metastasis - Suh, Yang-Gun; Bayasgalan, Unurjargal; Kim, Heung Tae; Lee, Jong Mog; Kim, Moon Soo; Lee, Youngjoo; Lee, Doo Yeul; Lee, Sung Uk; Kim, Tae Hyun; Moon, Sung Ho (Frontiers in Oncology, 2021)
Background and Purpose We compared treatment outcomes and toxicities of photon radiotherapy versus proton beam therapy (PBT) and evaluated radiation field effects for T1–3 squamous cell carcinoma of the thoracic esophagus (EC) without lymph node metastasis. Methods Medical records of 77 patients with T1–3N0M0 thoracic EC treated with radiotherapy between 2011 and 2019 were retrospectively analyzed. Among these patients, 61 (79.2%) individuals had T1 EC. The initial clinical target volume encompassed the whole esophagus with or without supraclavicular and/or abdominal lymph nodes (extended-field radiotherapy; 67 patients, 87.0%) or the area 3–5 cm craniocaudally and 1–2 cm radially from the gross tumor volume (involved-field radiotherapy; 10 patients, 13.0%). The final clinical target volume included margins of at least 1 cm from the gross tumor volume, with total radiation doses of 50–66 (median, 66) cobalt gray equivalent. Three-dimensional conformal radiotherapy, intensity-modulated radiotherapy, and PBT were used in twenty-four, five, and forty-eight patients, respectively. Concurrent chemotherapy was administered to 17 (22.0%) patients overall and only five (8.0%) T1 patients. Results PBT showed significantly lower lung and heart radiation exposure in mean dose, V5, V10, V20, and V30 than photon radiotherapy. The median follow-up for all patients was 46 (interquartile range, 22–72) months. The 5-year progression-free survival and overall survival rates were 56.5 and 64.9%, respectively, with no significant survival difference between photon radiotherapy and PBT. In patients with T1 EC, 5-year progression-free survival and overall survival rates were 62.6 and 73.5%, respectively. Conclusions Extended-field radiotherapy using modern radiotherapy techniques without chemotherapy showed satisfactory clinical outcomes for lymph node-negative T1 EC.